Analisis Data Berbentuk Teks dalam Sistem Diagnosis Penyakit dengan Supervised Learning - Ferry Mahayudha, I Gusti Ngurah Bagus; Dwidasmara, Ida Bagus Gede (Jurnal Nasional Teknologi Informasi dan Aplikasnya, 2023)
In  computer  science,  text  refers  to  a  sequence  of  characters  that  can  be  represented  and processed by a computer. It is the basic unit of data for representing human-readable information, such  as  letters,  numbers,  symbols,  and  spaces.  In  computer  programming,  text  is  typically represented as a string of characters. Textual data can be stored in variables, manipulated using various string operations, and displayed to users through input/output operations.Text plays a crucial  role  in  many  areas  of  computer  science,  including  natural  language  processing, information  retrieval,  data  mining,  and  text-based  communication  systems  like  email,  chat applications, and social media. It serves as a fundamental component for storing, analyzing, and processing vast amountsof textual information in various applications.